Development of an Analytical Method for Rapid Metal Determination in Stingless Bee Honey - Gislaine Pucholobek; Camila Kulek de Andrade; Sueli Pércio Quináia (Orbital: The Electronic Journal of Chemistry, 2021)
Stingless bee honey is a product used for different purposes due to its composition, in which the presence of metallic species is highlighted. Depending on their amount, they may have either a nourishing or a toxic effect. Flame atomic absorption spectrometry (FAAS) is a commonly used technique for quantifying metals in samples such as honey. However, because of the complexity of the matrix, the sample must go through a preparation step for the analytes to be available for quantification. In the present work, a fast and efficient sample preparation method for the quantification of metallic ions in stingless bee honey was optimized, from the direct analysis of slurries using FAAS. The samples were suspended using honey (1.0 g and 2.5 g), nitric acid (1.4 mol L-1 and 0.2 mol L-1), hydrogen peroxide (1% and 3%) and ultrasonic agitation (5 and 10 minutes). Then, the proposed analytical method was validated by evaluating parameters such as linearity, limits of detection and quantification, precision and accuracy, all with adequate values ​​compared to those established in the literature.DOI: http://dx.doi.org/10.17807/orbital.v13i2.1449